1998
DOI: 10.2134/jeq1998.00472425002700020016x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Kriging Methods Using Auxiliary Variables in Heavy‐Metal Contaminated Soils

Abstract: Characterization of the spatial distribution of pollutants in contaminated soils is important for risk assessment and soil reclamation. In this study, three kriging methods using auxiliary variables, cokriging, kriging combined with regression, and kriging combined with Q‐mode factor analysis, were used for interpolation of heavy metal concentrations in a contaminated site. The three interpolation methods were evaluated for whether or not they could make better use of an auxiliary variable for estimation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 0 publications
1
33
0
1
Order By: Relevance
“…The Ordinary Kriging interpolation method was used to characterize the spatial distribution of LABs in soils for assessing sewage contamination, which was carried out with ArcGIS 9.3 (ESRI, Redlands, California, USA) (Juang and Lee, 1998;Carlon et al, 2001;Hu et al, 2006Hu et al, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…The Ordinary Kriging interpolation method was used to characterize the spatial distribution of LABs in soils for assessing sewage contamination, which was carried out with ArcGIS 9.3 (ESRI, Redlands, California, USA) (Juang and Lee, 1998;Carlon et al, 2001;Hu et al, 2006Hu et al, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Juang and Lee (1998b) found that Pb, Cd, and Zn had very high correlation coefficients. They found that incorporating Pb and Cd concentrations as auxillary variables improved the interpolation of Zn.…”
Section: Determining the Spatial Distribution Of Phc Using Indicator mentioning
confidence: 95%
“…They found that incorporating Pb and Cd concentrations as auxillary variables improved the interpolation of Zn. Incorporating auxiliary variables into interpolations is the most advantageous when the primary or target variable is undersampled and there is a strong correlation between the variables (Juang and Lee 1998b;Goovaerts 1997;Deutsch and Journel 1998). This option was investigated to determine if utilizing the different fractions as co-variables would improve interpolation.…”
Section: Determining the Spatial Distribution Of Phc Using Indicator mentioning
confidence: 99%
“…In addition to semivariograms of individual variables, a cross-semivariogram is also used in traditional ordinary cokriging to quantify the cross-spatial correlation between the primary and secondary variable Z j and V k , respectively, shown as follows (Juang and Lee 1998):…”
Section: Ordinary Cokrigingmentioning
confidence: 99%